Driving Learning Policies and Legal Regulations for Transferring the Ancient Site Mission - Apichet Samerjai,; Supachai Chatjaruskool,; Nantana Sirichat,; Aphiradee Dononbao,; Kerkkai Norapan,; Naruechit Saenpakdee,; Kosin Attasophon,; Peerapol Simma, (Journal of Educational Issues, 2024)
The aim of the article is to drive learning policies and legal regulations for transferring the ancient site mission. The target groups performed in-depth interviews, group discussions, and comparative studies with neighboring communities. The study found that 1) the delegation policy lacked the impetus, decision-making, and clarity of the competent authority for future local government projects, and 2) problematic legal measures and barriers to the exploitation and management of archaeological sites at risk under The National Antiquities, Antiquities, Artefacts, and Museums Act 1961 and as amended (No. 2) B.E. 2535 (1992), influenced policy ideas favoring the transfer of management of historic places.